The perpendicular line will have the x and y coefficients swapped and one of them negated. We can write the desired line as
9(x -6) -3(y -4) = 0
where the coordinates of the point of interest are (6, 4).
Dividing by 3, this is
3(x -6) -(y -4) = 0
3x -y = 14
An equation for the line of interest is ...
3x -y = 14
the standard form of a quadratic formula is
y = ax^2 + bx + c
in this case you will solve using foil method
(× - 4)(x + 3)
<em>(</em><em>x</em><em> </em><em>×</em><em> </em><em>x</em><em>)</em><em> </em><em>+</em><em>(</em><em> </em><em>x</em><em> </em><em>×</em><em> </em><em>3</em><em> </em><em>)</em><em>(</em><em>-</em><em> </em><em>4</em><em> </em><em>×</em><em> </em><em>x</em><em>)</em><em> </em><em>(</em><em> </em><em>-4</em><em>)</em><em>×</em><em> </em><em>3</em><em>)</em><em>)</em>
<em>x</em><em>^</em><em>2</em><em> </em><em>+</em><em> </em><em>3x</em><em> </em><em>-</em><em> </em><em>4x</em><em> </em><em>-12</em>
<em>x</em><em>^</em><em>2</em><em> </em><em>-</em><em> </em><em>x</em><em> </em><em>-</em><em> </em><em>1</em><em>2</em>
<em>therefore</em><em> </em>
<em>y</em><em> </em><em>=</em><em> </em><em>x^</em><em>2-</em><em> </em><em>x</em><em> </em><em><u>-</u></em><em><u> </u></em><em><u>1</u></em><em><u>2</u></em><em><u> </u></em>
the correct answer is $948
Answer:
D. N(a) = (a + 20)/3
Step-by-step explanation:
A(n) = 3n - 20
A is a function of n. The inverse will be: N is a function of a.
Change A(n) to y and n to x.
y = 3x - 20
Switch x and y.
x = 3y - 20
Solve for y.
x + 20 = 3y
3y = x + 20
y = (x + 20)/3
Now switch y to N(a) and x to a.
Answer: N(a) = (a + 20)/3
Answer:
70
50
50
50
The easiest way to do it is to add the first digits then add the zero.
Hope that helps and have a great day!